The Effects of the Use of Corporate Derivatives on the Foreign Exchange Rate Exposure - Mohammad Al-Shbou; Stewart Alison (Journal of Accounting, Business and Management (JABM), 2009)
Corporate governance can provide mechanisms to effectively monitor the use of derivatives. In light of this, this study investigates the impact of the use of derivative on the foreign exchange-rate risk exposure with respect to the firm's ownership structure for a sample of 62 Australian multinational corporations. A two-stage market model is used. The first stage of this model is the use of a two-factor asset pricing model to estimate the foreign exchange exposure coefficients. The second stage of this model is the use of a cross-sectional regression model which regresses these estimated coefficients against the proxy for the use of derivatives with respect to the control variables such as the proxies for firm's ownership structure. The study finds that the use of foreign currency derivatives is associated with exposure reduction. The percentages of shares held by block-holders and institutions are found to be significantly positively related to foreign exchange risk exposure, while the percentages of shares held by directors are not significantly associated to exposure. Therefore, further research might explore the relationship between a firms ownership structure and its hedging activities more.